Eksplorasi Video YouTube sebagai E-Scaffolding pada Materi Matematika - Rofiki, Imam; Alfi Syahrin Siregar (MATHEdunesa, 2026)
Abstract: Technological advances in the 21st century have changed various aspects of human life, including education. One of the technological advances can be utilized as a scaffolding for students through YouTube videos. YouTube is the most frequently visited platform by internet users to learn about science. Scaffolding is assistance provided by more experienced people to others to be able to solve problems and reduce them gradually. Therefore, this study aims to explore YouTube videos as effective e-scaffolding in mathematics learning. This study uses a qualitative approach with an exploration type with thematic data analysis techniques. The data sources in this study are YouTube videos with the criteria of a minimum of 1000 viewers (views); (2) at least 50 comments; and at least 100 likes. The results of the study indicate that YouTube videos can assist students to understand and solve the problems given. E-scaffolding in this study is divided into two categories, namely local e-scaffolding and global e-scaffolding. Local e-scaffolding occurs when video content does not present arguments based on intrinsic mathematical properties, such as calculation tricks that are limited to a particular context. In contrast, global e-scaffolding provides assistance supported by arguments based on intrinsic mathematical principles, so that problem-solving strategies are more profound and generally valid.